A Theoretical Examination of Immigrant Status and Substance Use among Latino College Students. Issue 11 (2nd November 2019) - Grindal, Matthew; Admire, Amanda; Nieri, Tanya
ABSTRACT: Drawing on survey data from a sample of Latino college students, we examine the generalizability of social learning theory, general strain theory, social bond theory, and self-control theory to a Latino population and consider how these four theories can elaborate on the relationship between immigrant status and substance use. We find that social learning and general strain provide the most robust explanations of substance use across four outcomes. Also, third-plus generation respondents generally reported more substance use than first-generation respondents. Our findings suggest that this latter trend is due mostly to varying effect sizes in social learning by immigrant status.